Perlindungan Hukum Hak Ekonomi Pencipta dan Pemegang Hak Cipta Dalam Undang-Undang Nomor 28 Tahun 2014: Studi Kasus Putusan Nomor 820/PID.SUS/2021/PN.JKT.UTR - Cheva Alvessya, Dyvta (Jurnal Hukum Indonesia, 2026)
The increasing violations of economic rights of copyright holders highlight the urgent need for improved public awareness regarding copyright laws in Indonesia. This research examines the legal protection of the economic rights of creators and copyright holders under Law No. 28 of 2014, focusing on a case study involving PT Global Media Visual (Mola TV) and Hendri Gustijaya (defendant) in the 2021 court decision No. 820/Pid.Sus/2021/PN.Jkt.Utr. The study found that the violation occurred due to insufficient understanding of copyright, resulting in significant financial losses for the copyright holder. The methodology used was normative legal research, focusing on primary and secondary legal materials, including statutes and court rulings, collected through literature review. The analysis emphasizes the gap in public knowledge and the lack of education on copyright, which contributes to these violations. The research aims to contribute to raising awareness and preventing future copyright infringements, suggesting that further efforts in education and government intervention are essential for better protection of intellectual property rights. This study benefits stakeholders in the creative industry and law enforcement agencies by providing insights into the effectiveness of copyright laws in safeguarding economic rights. The findings suggest that strengthening legal awareness programs can significantly reduce violations.